Older Adults' Expectations about Mortality, Driving Life and Years Left without Driving. Issue 8 (17th November 2019) - Babulal, Ganesh M.; Vivoda, Jonathon; Harmon, Annie; Carr, David B.; Roe, Catherine M.; Zikmund-Fisher, Brian
ABSTRACT: People are living and driving longer than ever before, with little preparation for transitioning to being non-drivers. We investigated driving expectations among drivers age 65 and older, including sociodemographic and driving context predictors. Cross-sectional data from 349 older drivers were explored to determine variation in how many years they expected to continue driving. General linear models examined predictors of both expectations. In this predominantly Black/African American sample, 76% of older drivers (mean age = 73 ± 5.7 years) expected a non-driving future, forecasting living an average of 5.75 ± 7.29 years after driving cessation. Regression models on years left of driving life and years left to live post-driving cessation predicted nearly half of the variance in older drivers' expectations with five significant predictors: income, current age, age expected to live to, self-limiting driving to nearby places and difficulty, visualizing being a non-driver. Many older drivers expect to stop driving before end of life.